2004
DOI: 10.1128/iai.72.5.2689-2697.2004
|View full text |Cite
|
Sign up to set email alerts
|

CD4-T-Lymphocyte Interactions with Pneumolysin and Pneumococci Suggest a Crucial Protective Role in the Host Response to Pneumococcal Infection

Abstract: Previously, we had shown that T cells accumulated in peribronchiolar and perivascular areas of lungs soon after intranasal infection with Streptococcus pneumoniae. We have now presented new evidence, using major histocompatibility class II-deficient mice, that CD4 cells are important for early protective immunity. In addition, we have also shown that a population of human CD4 cells migrates towards pneumococci and that in vivo-passaged pneumococci are substantially more potent at inducing migration than in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
123
1
7

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(140 citation statements)
references
References 36 publications
9
123
1
7
Order By: Relevance
“…It is noteworthy that CD4 ϩ T cell-deficient mice that received CT only (and thus were naïve to pneumococci) were no more heavily colonized than CD8 ϩ T cell-deficient mice immunized with CT. These data, which do not indicate an important role for naïve CD4 ϩ T cells in the prevention of nasopharyngeal colonization, are in contrast with findings by Kadioglu et al (17) suggesting a role of naïve CD4 ϩ T cells in the protection against invasive disease. Overall, these results suggested that, after mucosal exposure to pneumococci, CD4 ϩ T cells may be required for protection against pneumococcal colonization.…”
Section: Prior Exposure To Homologous and Heterologous Capsular Serotcontrasting
confidence: 56%
See 2 more Smart Citations
“…It is noteworthy that CD4 ϩ T cell-deficient mice that received CT only (and thus were naïve to pneumococci) were no more heavily colonized than CD8 ϩ T cell-deficient mice immunized with CT. These data, which do not indicate an important role for naïve CD4 ϩ T cells in the prevention of nasopharyngeal colonization, are in contrast with findings by Kadioglu et al (17) suggesting a role of naïve CD4 ϩ T cells in the protection against invasive disease. Overall, these results suggested that, after mucosal exposure to pneumococci, CD4 ϩ T cells may be required for protection against pneumococcal colonization.…”
Section: Prior Exposure To Homologous and Heterologous Capsular Serotcontrasting
confidence: 56%
“…By contrast, in our colonization model, MHC Class II-deficient mice exposed to CT only (and thus naïve to pneumococcus) were no more heavily colonized than controls that lacked CD8 ϩ T cells. Thus, whereas Kadioglu et al (17) showed the importance of CD4 ϩ T cells in primary clearance of pneumococci during invasive disease in naïve mice, we have shown the involvement of CD4 ϩ T cells in a long-lasting, acquired immune response. Kadioglu et al (17,22) also showed that T cells are rapidly recruited after pneumococcal pulmonary infection and that human CD4 ϩ T cells migrate toward pneumococci in vitro, in a fashion that depends, at least in part, on the cytotoxin pneumolysin.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Our surprising observations on the immunity induced by i.n. vaccination with WCA were presaged by studies of pneumococci in naïve mice: the cellular response to pneumococcal infection had suggested a role of CD4+ T cells in the control of pneumonia and blood-borne infections (54), and the gradual clearance after intranasal challenge was similar in μMT −/− and normal animals (55). The observation that (human) children naturally increase their immunity to pneumococci of many serotypes simultaneously and before detectable capsular antibodies arise prompted our suggestion that an antibody-independent, CD4+ T cell-dependent process is an early contributor to natural pneumococcal immunity (53,56).…”
Section: Noncapsular Components As Immunogensmentioning
confidence: 99%
“…12,13 However, in populations at higher risk, such as infants and the elderly, this response may not be enough to clear the bacterium because of its intrinsic virulence factors that promote the evasion of the immune response. 9 Interleukin 10 (IL-10) is an anti-inflammatory cytokine that plays an important role in acute and persistent bacterial infections.…”
Section: Introductionmentioning
confidence: 99%